Shared Public Governance and Civic Competence Education: From Communicative Rationality to Co-Creative Power - Truong Quoc Viet (Social Science and Human Research Bulletin, 2026)
The expansion of public institutions, digital media, and governance techniques is occurring alongside a persistent gap betweenlegal rights and citizens' capacityfor substantive participation. This article aims to establish the theoretical foundations of shared public governance and clarify the role of education in the transformation from the right to political participation into a lived capability. The study adopts a human-sciences methodology and combines analytical, synthetic, deductive, inductive, logical, historical, critical, and structuralizing procedures. Its research materials include theoretical conceptions of participatory governance, collaborative governance, communicative rationality, civic education, participation rights, educational curricula, and school governance. The findings establish communicative rationality, the public sphere,citizenship, and co-creative power as constitutive elements of sharedpublic governance; identify the crisis of rationality and the erosionof agency as major constraints on substantive participation; position the school as a public sphere for forming civic competence; and develop a mechanism for institutionalizing participation rights through curricula, educators, school practices, family, community, and assessment. The article concludes that shared public governance ultimately depends on the capacity to transform legally recognized rights into autonomous, reasoned, and accountable action, thereby enabling citizens to participate meaningfully in shaping the shared conditions of collective life in contemporary public life.